Low-Dose Endothelial-Monocyte-Activating Polypeptide-II Induced Autophagy by Down-Regulating miR-20a in U-87 and U-251 Glioma Cells - Chen, Jiajia; Liu, Libo; Liu, Yunhui; Liu, Xiaobai; Qu, Chengbin; Meng, Fanjie; Ma, Jun; Lin, Yang; Xue, Yixue (Frontiers in Cellular Neuroscience, 2016)
Preliminary studies have shown that endothelial-monocyte-activating polypeptide-II (EMAP-II) induces autophagy and inhibits the viability of glioma cells via an unknown molecular mechanism. This study explored the possible mechanisms associated with EMAP-II-induced autophagy in glioma cells by regulation of the expression of microRNA-20a (miR-20a). EMAP-II effectively inhibited the viability, migration and invasion of human U-87 and U-251 glioma cells. EMAP-II also up-regulated the expression level of autophagy biomarker microtubule-associated protein 1 light chain 3(LC3)-II/I, autophagy related gene ATG7 and ATG5 , but down-regulated autophagy substrate P62/SQSTM1 protein expression. The expression levels of miR-20a decreased significantly after U-87 and U-251 cells were treated with EMAP-II. MiR-20a overexpression partly reversed the EMAP-II-induced up-regulation of LC3-II/I and down-regulation of P62/SQSTM1. MiR-20a had a negative regulatory effect on the expression of the proteins ATG7 and ATG5; which were also targets of miR-20a, as detected by a dual-luciferase reporter assay. In addition, both EMAP-II and miR-20a inhibition significantly reduced the viability, migration and invasion of U-87 and U-251 cells, and their combination showed a synergistic effect. Furthermore, nude mice carrying silencing-expressed miR-20a combined with EMAP-II treatment produced the smallest tumors and the highest survival. In summary, low-dose EMAP-II increased expression levels of ATG5 and ATG7 via down-regulation of the expression of miR-20a. This activated the autophagy pathway, thereby significantly inhibiting the viability, migration and invasion of U-87 and U-251 glioma cells. The combined treatment of EMAP-II with a miR-20a inhibitor showed a synergistic effect against glioma.